Inflammation alters the expression pattern of drug transporters during Caco‐2 cell stimulation and azoxymethane‐induced colon tumorigenesis - El‐Daly, Sherien M.; Gouhar, Shaimaa A.; Abdelrahman, Sahar S. (Journal of biochemical and molecular toxicology, 2024)
Drug transporters play a pivotal role in modulating drug disposition and are subject to alterations under inflammatory conditions. This study aimed to elucidate the intricate expression patterns of drug transporters during both acute and chronic inflammation, which are closely linked to malignant transformation. To investigate acute inflammation, we employed an in vitro model by subjecting Caco‐2 cells to various inflammatory stimuli (IL‐1β, TNF‐α, or LPS) individually or in combination. The successful induction of inflammation was confirmed by robust increases in IL‐6 and NO production. Notably, inflamed Caco‐2 cells exhibited significantly diminished levels of ABCB1 and ABCG2, while the expression of ABCC2 was upregulated. For chronic inflammation induction in vivo, we employed the well‐established AOM/DSS mouse model known for its association with colitis‐driven tumorigenesis. Persistent inflammation was effectively monitored throughout the experiment via elevated IL‐6 and NO levels. The sequential stages of tumorigenesis were confirmed through Ki‐67 immunohistochemistry. Intriguingly, we observed gradual alterations in the expression patterns of the studied drug transporters during stepwise induction, with ABCB1, ABCG2, and ABCC1 showing downregulation and ABCC2 exhibiting upregulation. Immunohistochemistry further revealed dynamic changes in the expression of ABCB1 and ABCC2 during the induction cycles, closely paralleling the gradual increase in Ki‐67 expression observed during the development of precancerous lesions. Collectively, our findings underscore the significant impact of inflammation on drug transporter expression, potentially influencing the process of malignant transformation of the colon. Acute and chronic inflammation alters the expression of specific drug transporters. Significant changes are detected in the expression of ABCB1, ABCG2, ABCC1, and ABCC2 in response to inflammation induced during the stepwise AOM/DSS tumorgenesis model. Drug transporters are crucial links between intestinal inflammation and tumorigenesis.